Correction of Class 2 malocclusion by means of a fully adjustable, virtually unbreakable, mandibular positioning (jumping) device - Prystupa, Ivan; Williams, Stephen; Loster, Bartłomiej W. (Journal of Stomatology, 2015)
Introduction. The construction and adaptation of the appliance to the individual patient is described and illustrated. The aim of the present report is to describe the development and clinical testing of an adjustable, unbreakable “bite-jumping” device, the “Flex Developer”® incorporating a nylon rod as the extendable “bite-jumping” element. Material and method. The report describes clinical testing on two groups of patients (young N = 17, mature N = 12) using a cephalometric appraisal before and after treatment. Results. The efficiency of the appliance in correcting Class II malocclusion by means a series of skeletal and dento-alveolar changes is clearly illustrated, the statistically significant skeletal improvement being greater in the younger (under 19 years) patients. Conclusion. The appliance constitutes a reliable adjunct to orthodontic correction of the Class II anomaly.